2020
DOI: 10.1039/c9sc06520b
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-inducing activity of a fluorescent barrel-rosette M+/Cl channel

Abstract: We report a 2-hydroxy-N1,N3-diarylisophthalamide-based self-assembled channel that cotransports M+/Cl− and induces apoptotic cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 85 publications
(106 reference statements)
1
20
0
Order By: Relevance
“…Cu uptake by HeLa cells is known to up regulate the production of reactive oxygen species (ROS) due to the high redox reactivity of copper, causing cytotoxicity in cancer cells [18] . In other reports, synthetic transporters have been shown to promote cell death by disrupting the balance of cellular ionic homeostasis [3i,k, 19] . Highly efficient Cu transporter molecules have also been known to serve as chemo‐sensitizers, whereby they enhance the efficacy of platinum anticancer drugs, such as cisplatin and carboplatin [20] .…”
Section: Resultsmentioning
confidence: 99%
“…Cu uptake by HeLa cells is known to up regulate the production of reactive oxygen species (ROS) due to the high redox reactivity of copper, causing cytotoxicity in cancer cells [18] . In other reports, synthetic transporters have been shown to promote cell death by disrupting the balance of cellular ionic homeostasis [3i,k, 19] . Highly efficient Cu transporter molecules have also been known to serve as chemo‐sensitizers, whereby they enhance the efficacy of platinum anticancer drugs, such as cisplatin and carboplatin [20] .…”
Section: Resultsmentioning
confidence: 99%
“…It is well‐documented in the literature that abnormally high ROS levels lead to the increased apoptosis in cancer cells by reducing the GSH levels . We had hypothesized that compound 2 works as a double‐edged sword to reduce the intracellular GSH levels by (i) getting activated into 1 b by reacting with GSH (Figure B), and (ii) increasing the ROS levels as a consequence of perturbation in ion homeostasis . Indeed, the GSH levels (as measured by 1 H NMR) in MCF‐7 cells treated with compound 2 (green) were significantly reduced when compared with the control cells (Figure E; red), thereby proving our hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…The same group also developed a barrel-rosette channel built from 2-hydroisophthalimides via H-bonds and π-π interactions, and capable of facilitating KCl or NaCl symport (Figure 9B). 90 The authors successfully confirmed the roles of both cation and anion transport towards apoptotic pathways in cells incubated with the 3,5-bis-trifluoromethylaryl derivative, and were able to visualise the compound within live cells using the intrinsic fluorescent properties of the channel.…”
Section: Self-assembled Ion and Water Channelsmentioning
confidence: 87%